Acoustical aspects of replacing traditional materials in building elements with renewable and recycled ones - Jiří Nováček; Jaroslav Hejl (Acta Polytechnica CTU Proceedings)
Building elements, especially partitions, floors and external walls significantly affect indoor acoustic comfort. Their ability to reduce noise transmission from neighbouring rooms or from outdoors depends on the element composition and the building materials used. In Central Europe, the heavyweight masonry or concrete walls and slabs are typical elements both for family and residential buildings. However, increasing popularity of lightweight multi-layered structures is noticeable. This creates new opportunities for the gradual replacement of traditional materials with renewable and recycled ones, both for load-bearing components and for fillings and other layers of building elements. This paper introduces such design changes in relation to acoustics, particularly airborne sound insulation. The greatest attention is paid to the replacement of masonry and mineral wool insulation with timber and wood fibres. The overview is supplemented by examples of low-energy house external wall and timber wall with recycled infill whose sound insulation has been determined by measurements in the acoustic laboratory.